2015
DOI: 10.1590/0102-37722015021711181191
|View full text |Cite
|
Sign up to set email alerts
|

Relacionamentos Afetivo-Familiares em Mulheres com Anorexia e Bulimia

Abstract: RESUMO -Este estudo teve por objetivo investigar a rede social de apoio de mulheres com anorexia e bulimia, com ênfase em suas relações afetivo-familiares. A amostra foi composta por 12 participantes atendidas em hospital universitário. Os instrumentos utilizados foram: roteiro de entrevista semiestruturada, Mapa de Rede e Genograma. Os resultados indicaram que as redes sociais das participantes têm configuração restrita, com proeminência de membros da família em sua composição. Os relacionamentos familiares o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 32 publications
0
7
0
18
Order By: Relevance
“…This shows that traumatic experiences generate negative psychological reverberations that may persist into the next generation, especially between family members who share the same gender. Several current studies have addressed the issue of psychic transmission among generations of families of members with ED (Leonidas & Santos, 2015aMoura, Santos, & Ribeiro, 2017;Valdanha-Ornelas & Santos, 2016).…”
Section: Attitudes Towards Sexuality Adverse Experiences and Its Relmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that traumatic experiences generate negative psychological reverberations that may persist into the next generation, especially between family members who share the same gender. Several current studies have addressed the issue of psychic transmission among generations of families of members with ED (Leonidas & Santos, 2015aMoura, Santos, & Ribeiro, 2017;Valdanha-Ornelas & Santos, 2016).…”
Section: Attitudes Towards Sexuality Adverse Experiences and Its Relmentioning
confidence: 99%
“…Therefore, it is not surprising that women with AN present difficulties to express themselves sexually, or even to develop intimate relationships, remaining isolated, anxious and emotionally withdrawn. However, for women with BN, both the relationship with food and the affectivesexual relationships are usually mediated by impulsive behaviours (Leonidas & Santos, 2015a), which are common traits among these women, along with comorbidity with Borderline Personality Disorder (Rosa & Santos, 2011). This shows that sexuality, as a multidimensional construct, is also influenced by personality traits.…”
Section: Introductionmentioning
confidence: 99%
“…Leonidas and Santos (2013;2015) assessed the social support networks of women with ED where results showed that family constituted their primary source of emotional (and physical) support. However, their personality traits impaired the quality of these relationships, engendering feelings of loneliness, undervalue, and lack of support.…”
Section: Circumstances Prior To Edmentioning
confidence: 99%
“…It is believed that participants considered family as the center of their interpersonal influence (Bullock, 2004;Leonidas & Santos, 2013;2015), and would like relationship patterns could become more healthy, contributing to the improvement of the ED.…”
Section: Expected Changesmentioning
confidence: 99%
“…Apesar de ainda não existir um consenso a respeito da origem desses quadros, reconhece-se que a etiologia envolve a interação dinâmica de vários fatores, tanto intrínsecos quanto extrínsecos ao indivíduo (King, Gerish & Schreiber, 2019;Oliveira-Cardoso & Santos, 2012). Tais fatores combinados dão início, precipitam e/ou mantêm o transtorno, gerando alterações em vários aspectos da vida pessoal, dentre eles os relacionamentos interpessoais e afetivo-sexuais -uma vez que a vulnerabilidade emocional dificulta o estabelecimento e a preservação de vínculos (Leonidas & Santos, 2015a).…”
Section: Introductionunclassified